PEMBENTUKAN KARAKTER DISIPLIN SISWA MELALUI PENERAPAN TATA TERTIB SEKOLAH DI SEKOLAH MENENGAH PERTAMA ISLAM DARUSSA’ADAH PONCOKUSUMO MALANG - Ilham Ali Yafie; Chalimatus Sa’dijah; Mohammad Murtadho (VICRATINA, 2020)
The character of discipline is something everyone needs to have. Because with a character discipline can make a person's life become more organized and orderly in all aspects. The goal in shaping the character of discipline is to develop a person's basic potential to behave orderly and orderly in everyday life. Research titled "Character Building Discipline of students through the application of school order at the Islamic Junior High school Darussa'adah Poncokusumo Malang" with the aim of knowing the rules of order applied in the Islamic Junior High school Darussa'adah Poncokusumo and strategies in implementing school order to form students ' disciplinary character in the school. Researchers do research with qualitative methods with this type of case study research. In this research, it is found that the state of the Order of school in Islamic Junior High school Darussa'adah Poncokusumo includes 3 main contents in the form of: 1). Types of school rules. 2). Types of violations and actions. 3). Sanctioned violations. The strategies undertaken by the school in implementing the school order to form the character discipline are socialization, habituation, transparency, supervision, sanctions (punishment), evaluation. These strategies have resulted in good results, the increasing discipline of the students from previous times.